H. M. RASJIDI (1915-2001) ON MORALITY AND ITS RELEVANCE TO CONTEMPORARY DISCOURSE - Azani, Mohammad Zakki (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2019)
This paper elaborates on the significant roles of H. M. Rasjidi?s thoughts on morality. In it, re-affirming one of the fundamental principles of Islam which is the metaphysical foundation of morality. This is also an attempt to expose the relative values of the morality which have been developed by Western modern philosophers. Rasjidi explains that morality in Islam is not only decided by cultural consensus and social fitness but it is also quite related to the nature of man?s existence. By realizing that, it would lead a Muslim to be always conscious that morality or good deed is intimately dependent on the fundamental principles of Islam. Thus, Rasjidi?s view towards a good thing which is found from diverse cultures and civilizations has to be and still need to be interpreted in light of the intellectual framework of Islam.